The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1088/0953-8984/15/19/310
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-one-dimensional polaronic states due to the preferential reduction in the LixV3O8insertion electrode

Abstract: The structural and electronic properties of the Li1+xV3O8 insertion electrode, where 0 ≤ x < 0.4, have been explored by means of x-ray four-circle diffraction and through measurements of electrical resistivity, thermoelectric power, magnetization and electron paramagnetic resonance. Detailed structure refinements for x = 0.06 and 0.29 reveal the preferential and partial reduction of V ions which may give rise to low-dimensional electronic properties. The composition with x = 0 exhibits a quasi-one-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 18 publications
(32 reference statements)
2
34
1
Order By: Relevance
“…Since this material is empirically observed to be a semiconductor over the entire concentration range, we need to choose a large enough value of U such that all structures become semiconducting. The experimental measurement of Li1V3O8 single crystal 62 indicates a small bandgap of approximately 0.1eV, which is smaller than the value predicted by either DFT or DFT+U calculations for Li1V3O8 where the band gap is approximately 1.0eV. However, for higher values of lithiation, Li1+xV3O8, we can technically open a small gap within the 3d band with appropriate U for each configuration.…”
Section: A Electronic Structurementioning
confidence: 65%
See 2 more Smart Citations
“…Since this material is empirically observed to be a semiconductor over the entire concentration range, we need to choose a large enough value of U such that all structures become semiconducting. The experimental measurement of Li1V3O8 single crystal 62 indicates a small bandgap of approximately 0.1eV, which is smaller than the value predicted by either DFT or DFT+U calculations for Li1V3O8 where the band gap is approximately 1.0eV. However, for higher values of lithiation, Li1+xV3O8, we can technically open a small gap within the 3d band with appropriate U for each configuration.…”
Section: A Electronic Structurementioning
confidence: 65%
“…The electron donated from lithium intercalates into toptactic compound to form an electron polaron which hops from one transition metal ion to another. In particular, M Onoda 62 found small polorans mainly exist on the V(2) and V(3) sites due to preferential reduction. In another study, Florent Boucher 64 also showed a preferential reduction sequence V(3)>V( 2)>V( 1) upon lithiation from XPS data.…”
Section: A Electronic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Charge carriers are small polarons which move along vanadium chains parallel to the b-axis. 36 Noteworthily, Onoda et al have obtained the same activation energy by dc-conductivity measurements on a Li 1.1 V 3 O 8 single crystal. Nevertheless the s p value obtained here is 110 times lower than that measured along the b-axis in a Li 1.1 V 3 O 8 single crystal.…”
Section: Electronic Transport Properties and Dielectric Relaxationsmentioning
confidence: 81%
“…31,32 A great deal of interest has been focused on the structural characterization and cyclability of this compound. [33][34][35] Onoda and Amemiya 36 have shown that Li 1.1 V 3 O 8 exhibits a quasi-one dimensional polaronic transport along vanadium chains (from V IV to V V ) parallel to the b-axis. The lithium self-diffusion coefficient D Li of about 5.6 Â 10 À12 to 9 Â 10 À12 cm 2 s À1 at RT was previously determined by 7 Li NMR.…”
Section: Introductionmentioning
confidence: 99%